Issues In Translating Military Terms And Texts Between English And Arabic - Ai-Shehab, Mohammad Hamza (2009)
This study is aimed at exammmg the ability of military personnel involved in translation work in the Jordanian Military Academy to translate terms and expressions within the context of military texts from English into Arabic. It is also aimed at investigating the problems confronting military personnel when translating military texts from English to Arabic and vice versa.